2010
DOI: 10.1068/p6627
|View full text |Cite
|
Sign up to set email alerts
|

When You Turn the other Cheek: A Preference for Novel Viewpoints of Familiar Faces

Abstract: Inferences about the psychobiological processes that underlie face perception have been drawn from the spontaneous behaviour of eyes. Using a visual paired-comparison task, we recorded the eye movements of twenty adults as they viewed pairs of faces that differed in their relative familiarity. The results indicate an advantage for novel viewpoints of familiar faces over familiar viewpoints of familiar faces and novel faces. We conclude that this preference serves the face recognition system by collecting the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…While it is well-known that in-plane rotations, eg inverting a face 1808, result in impaired recognition of both Effect of familiarity and viewpoint on face recognition in chimpanzees familiar and unfamiliar faces (Johnston and Edmonds 2009;Rossion 2008;Valentine 1988;Yin 1969), changes in facial viewpoint appear to selectively impair the ability to recognize unfamiliar faces (Bruce 1982;Hancock et al 2000;Hill et al 1997;Johnston and Edmonds 2009;McKone 2008). It has even been suggested that two different unfamiliar faces presented in the same view may appear more perceptually similar to one another than the same face presented across two different views (Favelle et al 2007;Taubert et al 2010). These findings have led to the suggestion that unfamiliar faces are processed in a viewpoint-dependent manner, ie recognition is dependent on the viewpoint encountered, whereas familiar faces are processed in a more viewpointindependent manner, ie recognition survives changes in facial viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…While it is well-known that in-plane rotations, eg inverting a face 1808, result in impaired recognition of both Effect of familiarity and viewpoint on face recognition in chimpanzees familiar and unfamiliar faces (Johnston and Edmonds 2009;Rossion 2008;Valentine 1988;Yin 1969), changes in facial viewpoint appear to selectively impair the ability to recognize unfamiliar faces (Bruce 1982;Hancock et al 2000;Hill et al 1997;Johnston and Edmonds 2009;McKone 2008). It has even been suggested that two different unfamiliar faces presented in the same view may appear more perceptually similar to one another than the same face presented across two different views (Favelle et al 2007;Taubert et al 2010). These findings have led to the suggestion that unfamiliar faces are processed in a viewpoint-dependent manner, ie recognition is dependent on the viewpoint encountered, whereas familiar faces are processed in a more viewpointindependent manner, ie recognition survives changes in facial viewpoint.…”
Section: Introductionmentioning
confidence: 99%